2020
DOI: 10.1007/s40257-020-00545-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of Clinician-Reported Outcome (ClinRO) and Patient-Reported Outcome (PRO) Measures for Eyebrow, Eyelash and Nail Assessment in Alopecia Areata

Abstract: Background Eyebrow and eyelash hair loss and nail damage-in addition to scalp hair loss-are important signs/symptoms of alopecia areata (AA) to patients and deserve assessment in AA clinical trials. Objectives Our objective was to develop clinician-reported outcome (ClinRO) and patient-reported outcome (PRO) measures and accompanying photoguides to aid in the assessment of AA-related eyebrow, eyelash and nail signs/symptoms. Methods Iterative rounds of qualitative, semi-structured interviews were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 18 publications
2
54
0
Order By: Relevance
“…Interview results were aligned with those in North America [ 26 , 27 , 29 ]. All clinicians and nearly all patients confirmed that scalp hair loss was the most important AA sign/symptom and scalp hair regrowth was the greatest treatment priority.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interview results were aligned with those in North America [ 26 , 27 , 29 ]. All clinicians and nearly all patients confirmed that scalp hair loss was the most important AA sign/symptom and scalp hair regrowth was the greatest treatment priority.…”
Section: Discussionsupporting
confidence: 55%
“…Clinician-reported outcome (ClinRO) and PRO measures [ 29 ] (see Fig. S1 in the “Supplementary Information”) were also developed to assess key secondary AA signs/symptoms [ 30 ], including the ClinRO Measure for Eyebrow Hair Loss™, PRO Measure for Eyebrows™, ClinRO Measure for Eyelash Hair Loss™, PRO Measures for Eyelashes™, ClinRO Measure for Nail Appearance™, PRO Measure for Nail Appearance™, and PRO Measure for Eye Irritation™.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a comprehensive suite of content-valid clinical outcome assessments of the key physical effects of AA were developed as part of this study. Development of an investigator global assessment [43] and PRO measure [27] for scalp hair loss, along with ClinRO and PRO measures for eyebrow loss, eyelash loss, nail appearance and eye irritation [28] are reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative study was designed to elicit the patient experience of AA and to develop and cognitively test PRO measures for key physical AA signs/symptoms (results of this latter objective are reported elsewhere [27,28]). The study protocol was reviewed and approved by Western Institutional Review Board (ref #20171820).…”
Section: Ethicsmentioning
confidence: 99%
See 1 more Smart Citation